An Interpretation of social values and standards by youth - a comparative analysis. - Janina Florczykiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The issue showed in the text is about social values and standards considered as a social control factor. Their internalization is an expression of the level of moral development. It conditions the observation of social cohabitation rules.         The presented researches show an issue of subjective interpretation of values and standards, comparative analysis declared by socially adapted and unadapted youth values. The results widen the knowledge of the range of youth values system and its connections with Social Maladjustment and show directions of youth educational interactions.